Height Gain Prediction in Adolescent Idiopathic Scoliosis Based on Preoperative Parameters. Issue 8 (19th September 2021) - Smorgick, Yossi; Tamir, Eran; Mirovsky, Yigal; Rabau, Oded; Lindner, Dror; Anekstein, Yoram
Abstract : Background: The purpose of the study was to identify preoperative parameters which are associated with height gain after corrective surgery for adolescent idiopathic scoliosis (AIS) and their use to preoperatively quantify the potential for height gain after AIS correction. Methods: Our study included 87 consecutive patients with AIS who underwent posterior fusion. Patients' height was measured the day before surgery and before their discharge. Demographic and radiologic variables were analyzed for predictability of height gain. Results: The mean height gain was 3.85 cm. We have found a statistically significant correlation between height gain and the following measures: preoperative thoracic curve, preoperative thoracolumbar curve, preoperative thoracic kyphosis, flexibility of the main thoracic and thoracolumbar curves, and number of fused levels (all P <0.05). Patients with Lenke type 1 and 2 had statistically less height gain compared with patients with Lenke type 3, 4, 6. Conclusion: Most of the scoliosis patients with Lenke type 1 and 2 will gain up to 3 cm after surgery while most of the patients with Lenke type 3, 4, 6 will gain more than 3 cm. Most patients with Lenke type 3, 4, 6 with a major curve of less than 60 degrees will gain up to 4 cm, while most of those with a major curve of more than 60 degrees will gain more than 4 cm. Patient with a positive thoracic sagittal modifier tend to have more height gain after surgery.